069 Co-existent autoimmune disease in AQP4-IgG, MOG-IgG and seronegative NMOSD. Issue 6 (27th May 2022) - Linaker, Samantha; Kelly, Patricia; Gibbons, Emily; Campagna, Giovanna; Whittam, Daniel; Karthikeayan, Venkatra- man; Mutch, Kerry; Jacob, Anu; Huda, Saif
Abstract : Background: Neuromyelitis Optica Spectrum Disorder (NMOSD) is an autoimmune inflammatory disorder of the central nervous system (CNS), and in most cases is associated with Aquaporin-4 antibodies (AQP4- IgG). Severe optic neuritis, longitudinally extensive myelitis and brain involvement is characteristic. Similarly presenting patients may not have detectable AQP4-IgG (seronegative NMOSD) or have Myelin Oligo- dendrocyte Glycoprotein IgG (MOG-IgG). Method: A retrospective study of AQP4-IgG, MOG-IgG, and seronegative NMOSD patients attending the highly specialised NMOSD service between September 2010-August 2019 was performed. In particular, the presence of coexistent autoimmunity was assessed. Results: Coexistent autoimmunity in AQP4-IgG patients was higher as compared to MOG-IgG and seron- egative NMOSD (30% vs. 8% vs. 8%). Some AQP4-IgG patients had 2nd and 3rd autoimmune diseases (7% and 1% respectively). In contrast no patients with MOG-IgG or seronegative NMOSD had 2 or more other autoimmune diseases. Conclusion: Coexistent autoimmunity in AQP4-IgG NMOSD is more common that in seronegative NMOSD and patients with MOG-IgG. It is reasonable to periodically assess for coexistent autoimmunity in AQP4-IgG NMOSD as it is present in almost a third of patients. Finally the detection of ≥2 autoimmune diseases in newly presenting cases provides a useful clue to AQP4-IgG NMOSD whilst antibody results are awaited. giovanna.campagna@thewaltoncentre.nhs.uk